Tetraloop-like geometries could form the basis of the catalytic activity of the most ancient ribooligonucleotides - Stadlbauer, Petr; Šponer, Jiří; Costanzo, Giovanna; Di Mauro, Ernesto; Pino, Samanta; Šponer, Judit E (Chemistry (Weinheim an der Bergstrasse, Germany), 2015)
The origin of the catalytic activity of ancient oligonucleotides is a largely unexplored field of contemporary science. In the current work we use molecular dynamics simulations to investigate the plausibility of tetraloop-like overhang geometries to initiate transphosphorylation reactions that lead to ligation and terminal cleavage in simple, Watson-Crick (WC) complementary oligoC/oligoG sequences observed experimentally. We show a series of examples of known tetraloop architectures, which can be adopted by the unpaired overhangs of short oligonucleotide sequences for a sufficiently long time to enable chemical reactions that lead to simple ribozyme-like catalytic activity. Thus, our computations demonstrate that the role of non-WC interactions at the emergence of the most ancient catalytic oligonucleotides could be more significant than ever believed.
Keywords: RNA, Catalytic; Catalysis; ribozymes; sekvence nukleotidů; Molecular Dynamics Simulation; Base Sequence; kinetika; simulace molekulární dynamiky; Oligonucleotides; oligonukleotidy; RNA katalytická; RNA; catalysis; molecular dynamics; oligonucleotides; Kinetics; katalýza